Individual counseling. - A. Hamid, Siti Zubaidah (Universiti Sains Malaysia, 1990)
Individual Counseling is considered the heart of the counseling function.This role is perhaps the most visible aspect of the counselor's work and what most people think of when they imagine a counselor at work.